The Leibholz-Schmitt connection's formative influence on Bonhoeffer's 1932-33 entry into public theology - Radler, Karola (Stellenbosch Theological Journal, 2018)
Dietrich Bonhoeffer's brother-in-law Gerhard Leibholz's insight into the Fascist theory of the states' messianic leadership and myth of creating communal life became a major source of information for Bonhoeffer. Leibholz had gained this knowledge in close jurisprudential cooperation with Carl Schmitt as is evidenced by Leibholz's 1929 habilitation thesis which at the same time intersected with Bonhoeffer's academic work. Their original political leanings towards authoritarianism, Volk, and Vitalism were revised by Bonhoeffer and Leibholz in November 1932 through stepping out into a coordinated public opposition to the approaching political changes. But both only recognized the populist xenophobic destructiveness of such a life, hidden beneath the myth of unity, once Schmitt turned to National Socialism in early 1933. Bonhoeffer's theology, built on the Leibholz-Schmitt discourse, remains a call for vigilance against the abuse of power, populism, and xenophobia, and continues to call for seeking God-revealed life.